Why is Measured Productivity so Low in Agriculture? - Berthold Herrendorf; Todd Schoellman (Center for Economic Studies and ifo Institute (CESifo), 2015)
In poor countries, labor productivity in agriculture is considerably lower than in the rest of the economy. We assess whether this well known fact implies that labor is mis-allocated between the two sectors. We make several observations that suggest otherwise. First, the same fact holds for US states where severe mis-allocation is implausible. Second, the gaps between the marginal value products of agriculture and non-agriculture are considerably smaller when measured through wages than through labor productivities. Third, labor productivity in agriculture is severely mis-measured in the US.
Keywords: O10; 330; mis-allocation of labor; productivity gaps; wage gaps